Trace oxophilic metal induced surface reconstruction at buried RuRh cluster interfaces possesses extremely fast hydrogen redox kinetics. (December 2021) - Cui, Yujia; Xu, Zihan; Chen, Ding; Li, Tingting; Yang, Hao; Mu, Xueqin; Gu, Xiangyao; Zhou, Hong; Liu, Suli; Mu, Shichun
Abstract: Developing high-efficiency electrocatalysts is the key to generating and consuming hydrogen by accelerating the reaction kinetics of the hydrogen oxidation and evolution reactions (HOR/HER). Although the kinetics process of the adsorbed intermediates (Had )-water-oxophilic metal has been investigated in the alkaline media, the hydroxyl species (Had or OH - or OHad )-activity relationship for oxophilic metal alloy electrocatalysis during multiple HOR and HER processes is still unclear. In this regard, our density functional theory (DFT) calculation results show that, due to partial substitution of Ru (Rh) clusters at buried interfaces by oxophilic-metal (OM) species, the long-range order of Ru (Rh) clusters surface atoms can be broken, and then the active atom reconstruction at buried interfaces is triggered, which decreases the oxidation intermediates of Ru (Rh) and gives rise to the increased activity for alkaline HER/HOR. At the same time, an OH - -adsorption promoter forms, also favorable for OER. Encouraged by the ﬁrst-principles calculation results, an ultralow-loaded OM species (0.13 wt% Co, 0.23 wt% Mn, 2.4 wt% Cr or 1.3 wt% Fe) incorporated RuRh cluster (RuRh-OM) catalyst is built by a mixed-solvent strategy. Impressively, after incorporating OM (Co; Mn; Cr and Fe), these catalysts exhibit higher HOR activity than pristine RuRh and commercial Pt even at higher potentials in 0.1 M KOH solutions, which outperforms most reported HOR catalysts and 2 times higher than that of commercial Pt. Meanwhile, RuRh-Co also exhibits the highest HER activity among all reported Ru-based HER catalysts, and greatly improved OER and overall water spitting performances in alkaline solutions (1 M KOH for HER and overall water spitting, 0.1 M KOH for OER), exceeding RuRh and commercial noble metal catalysts. Graphical Abstract: Our theoretical calculation results demonstrate that both the release of a greater number of active Ru (Rh) atoms can enhance the HOR kinetics via substituting partial Ru (Rh) clusters with oxophilic-metal species at buried interfaces. Accordingly, a series of ultralow-loaded oxophilic metal species (OM = Co, Mn, Cr or Fe) incorporated RuRh cluster (devoted as RuRh-OM) catalyst is built, displaying unprecedented multi-functional electrocatalytic HOR/HER/OER activity. ga1 Highlights: DFT calculation verifies reduced oxidation intermediates of Ru(Rh) for HER/HOR. Ultralow-loaded oxophilic metal incorporated RuRh cluster (RuRh-OM) is built. RuRh-OM (OM=Co, Mn, Cr and Fe) exhibits higher HOR activity than Pt catalysts. RuRh-Co has the highest HOR mass activity and exchange current density. RuRh-Co also reveals greatly improved OER and overall water spitting performance.